Analysis of platelet‐reactive alloantibodies and evaluation of cross‐match‐compatible platelets for the management of patients with transfusion refractoriness. Issue 1 (18th May 2017) - Wang, J.; Xia, W.; Deng, J.; Xu, X.; Shao, Y.; Ding, H.; Chen, Y.; Liu, J.; Chen, D.; Ye, X.; Santoso, S.
SUMMARY: Background: Cross‐match‐compatible platelets can improve corrected count increments (CCIs) in alloimmunised patients with transfusion refractoriness. However, only a few studies mentioned that the specificities of platelet‐reactive alloantibodies can predict high reactivity in cross‐match assays among these patients. Methods: A total of 204 medical records of patients who were refractory to random single‐donor apheresis platelets between January 2014 and December 2014 were enrolled. Platelet‐reactive antibodies in patients' serum were screened by an enzyme‐linked immunosorbent assay (ELISA).The platelet cross‐match assays were performed by a solid‐phase adherence assay. The specificities of human leukocyte antigen (HLA) class I and human platelet antigens (HPAs) alloantibodies were determined by Luminex Single Antigen and Monoclonal Antibody‐specific Immobilization of Platelet Antigens (MAIPA) assays, respectively. Results: Anti‐HLA and anti‐HPA alloantibodies were found in 114 of 204 (55.88%) patients, including 110 (96.49%) with anti‐HLA alloantibodies only, 2 (1.75%) with anti‐HPA alloantibodies (anti‐GPIIb/IIIa) only and 2 (1.75%) with both anti‐HLA and anti‐HPA alloantibodies (anti‐HPA‐3a and anti‐HPA‐5b). The most common HLA class I alloantibody phenotypes in cross‐match‐incompatible patients were HLA‐A23 (59.38%), ‐A24 (50.00%), ‐A02 (43.75%), ‐B27 (65.63%), ‐B40 (50.00%), ‐B18 (46.88%) and ‐B07 (43.75%). A total of 480 cross‐matched platelet units were administered in 82 of 114 alloimmunised patients with a mean CCI of 7800 ± 5200, a significant improvement over random platelet units ( P < 0.001). Conclusions: No development of additional platelet alloantibodies was observed during this platelet transfusion regiment. This study showed that transfusion of cross‐match‐compatible platelet units offers effective and safe management of platelet transfusion refractoriness (PTR). The finding of alloantibodies among cross‐match‐incompatible cases can be used as predictors for platelet donor selection.